Effect of mulch materials on potato production and soil properties in high hill of Parbat, Gandaki Province, Nepal - Timilsina, Sandip; Khanal, Asmita; Timilsina, CK; Poon, TB (Journal of Agriculture and Natural Resources, 2022)
An experiment for two consecutive years (2017 and 2018) was conducted to evaluate the use of mulching materials in increasing productivity and profitability of potato production. The experiment was conducted in Randomized Complete Block Design (RCBD) with five different mulching materials including control replicated for four times namely, banmara (Agertina adenophora) weed (T1), black polythene sheet (T2), white polythene sheet (T3), commercially used mulch paper having black color outside and silver color inside (T4) and farmers practice (T5) as a control with no mulch. The research result revealed that all the mulching materials significantly (p value ≤ 0.05) increased tuber yield and yield attributing characters of potato as compared with control (no mulch). The highest tuber yield was obtained from mulching with commercial mulch paper followed by mulching with black polythene sheet in both years. Mulching with banmara also produced significantly (p value ≤ 0.01) higher tuber yield than no mulch plot in the year 2017 and 2018. Mulching practices significantly (p value ≤ 0.05) improved the soil available phosphorus. The incremental benefit cost ratio was highest (2.97) in the mulched with banmara followed by commercial mulch paper (2.12). The banmara mulch was also profitable with comparatively higher tuber yield.